Comparative Study of the Production and Marketing of Onions in Three Regions of Libya - EL-WIFATI, BASHIR; NAWAS, FARID (The Libyan Journal of Agriculture, 2023)
The onion is an important winter vegetable crop in Libya. It is grown for consumption in the green state and as dry bulbs. Its production is geographically concentrated in three regions: Tripoli, Jalue and Sebha. This study was conducted in March and April of 1979 in order to compare the production and marketing problems confronting onion growers in the three regions, and to ascertain feasible solutions for them. Personal interviews by the extension agents in the various regions were conducted with random samples of 130, 23 and 42 farmers in Tripoli, Jalue and Sebha, respectively. The farmers were asked to fill out a questionnaire designed specifically for this study. The study showed that areas allocated for onion growing varied from one region to another and from year to year due to price fluctuations, storage problems, and other reasons. Early Texas Grano (502) is the most common variety in the Tripoli region. This variety does not withstand storage for long periods and arrangements should be made to encourage onion seed production locally, or to import varieties suited to local conditions and tolerant to storage. Adequate cold storage facilities should also be provided. The role of agricultural co-operatives in the production and marketing of the onion crop is minor. They could play a greater part in supplying farmers with production inputs, and in the co-operative marketing of the produce. Cleaning, sorting and packaging of onions prior to marketing is done by the farmers in all regions. Finally, most farmers from all regions indicated that they planned to expand onion production in the future, if major production and marketing problems are solved.